Liquid spring damper for vertical landing Reusable Launch Vehicle under impact conditions. (15th April 2019) - Yue, Shuai; Titurus, Branislav; Nie, Hong; Zhang, Ming
Highlights: Development of an enhanced nonlinear lumped parameter model for liquid spring damper. Experimental evaluation of Reusable Launch Vehicle prototype with four landing legs. Parameter identification across four liquid spring dampers and multiple conditions. Analysis of the model predictive quality under quasi-static and impact conditions. Abstract: This research presents the modelling, experimental validation and analysis of the liquid spring damper under impact conditions during the symmetric vertical soft landing of a Reusable Launch Vehicle. A new nonlinear lumped parameter hydraulic model of a liquid spring damper is first established including the variable liquid bulk modulus, entrapped air, flow inertial effects and cavitation phenomena. Then, a simplified nonlinear model of the scaled Reusable Launch Vehicle test prototype is proposed. This dynamic model, which consists of a three degree-of-freedom main body and a single landing leg assembly with one liquid spring damper, is studied under impact conditions. The experimental prototype with the four nominally identical landing legs is experimentally studied. First, the quasi-static spring damper tests are conducted to identify the compressibility and friction parameters. Then, the Reusable Launch Vehicle prototype drop tests are performed to identify the liquid flow parameters, to validate the damper impact response characteristics and to evaluate the full prototype model through its comparison with the experimental data. It is found that a very good match can be established between the predicted and measured quasi-static damper responses. The local damper predictions also indicate good correlation with the impact test results. The landing prototype simulations indicate qualitatively correct predictions with the main observed discrepancies attributed to the simplified and potentially excessively stiff nature of the prototype model.